Robot-Assisted Laparoscopic Pyeloplasty in a Pediatric Patient with Horseshoe Kidney: Surgical Technique and Review of the Literature. Issue 1 (January 2017) - Oderda, Marco; Calleris, Giorgio; Allasia, Marco; Dalmasso, Ettore; Falcone, Marco; Catti, Massimo; Merlini, Emilio; Gontero, Paolo
Objective: The aim of this study was to describe the technical aspects of a robotic pyeloplasty in pediatric patients with uretero-pelvic junction obstruction (UPJO) in horseshoe kidney (HSK) through the report of our recent case, and to outline the state of the art of minimally invasive pyeloplasty (MIP) with a systematic review of the literature. Methods: We describe all the steps of our surgery performed on an 11-year-old patient with left UPJO in HSK in detail. All the anatomic landmarks are clearly showed, with particular attention to trocar placement in a pediatric patient. A systematic review of the literature on the outcomes of MIP in HSK patients has been performed, including 16 articles. Results: Our surgery was successful following a standardized approach. However, we recorded a rare complication, the herniation of a small portion of omentum through the 8 - mm defect used for the caudal robotic port. The evidence synthesis shows excellent postoperative outcomes for both laparoscopic and robot-assisted laparoscopic pyeloplasties in HSK patients. Probably, MIP should be preferred to the traditional open approach in these patients, when feasible. Conclusions: Transperitoneal robotic pyeloplasty is an excellent minimally invasive choice for the treatment of UPJO in HSK pediatric patients. The pediatric setting should prompt attention to every detail to avoid unfortunate complications.